A taxonomic study of Chinese Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) (I) - Qin, Dao-Zheng; Liu, Yang; Zhang, Ya-Lin (Zootaxa, 2010)
A new genus of Chinese Empoascini (Hemiptera: Cicadellidae: Typhlocybinae), Radicafurcus Qin & Zhang, gen. n. with one new species, R. breviprocessus Qin & Zhang, sp. n. from Sichuan Province (S.W. China) is described and illustrated. Baguoidea Mahmood 1967 is redescribed and a new species, B. yunnanensis Qin & Zhang, sp. n. is described from Yunnan Province (S.W. China). Two genera (Faiga Dworakowska 1980 and Sikkimasca Dworakowska 1994) are reported for the first time from China, and the type species of these genera are re-illustrated.